2010
DOI: 10.1016/j.biocon.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of plant diversity on people’s perception and aesthetic appreciation of grassland vegetation

Abstract: The influence of plant diversity on people's perception and aesthetic appreciation of grassland vegetation AbstractThe conservation of biodiversity critically depends on the value that humans attach to it. Apart from an ecological and economic value, an aesthetic value has often been assigned to biodiversity. However, it is not known whether lay people appreciate the diversity of species and not just certain individual species or nature as a whole. We studied in a series of experiments and field studies people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
150
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(179 citation statements)
references
References 56 publications
15
150
3
2
Order By: Relevance
“…When flower diversity was experimentally increased in small public gardens in Paris, the visitors did not perceive any change in diversity before and after the manipulation although the participants expressed a preference for species richness (Shwartz et al 2014). In another experimental study, Lindemann-Matthies et al (2010) found that lay people appreciated species-rich, high-diversity grass communities more than species-poor ones. However, their study was performed on a rather small scale.…”
Section: Introductionmentioning
confidence: 90%
“…When flower diversity was experimentally increased in small public gardens in Paris, the visitors did not perceive any change in diversity before and after the manipulation although the participants expressed a preference for species richness (Shwartz et al 2014). In another experimental study, Lindemann-Matthies et al (2010) found that lay people appreciated species-rich, high-diversity grass communities more than species-poor ones. However, their study was performed on a rather small scale.…”
Section: Introductionmentioning
confidence: 90%
“…The visual character of landscapes affects human well-being in different ways, especially in terms of aesthetic appreciation, human health, and human relations [6][7][8]. Hence, an attractive environment can support a positive future development in Europe's mountain areas, especially, in terms of economic benefits related to tourism, as mountain landscapes are appealing environments [4,[9][10][11]. Scenic beauty assessments and modeling approaches, which consider recent landscape dynamics, can support the local decision makers and landscape planners towards a sustainable development [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…The biological dimension includes evolutionary principles, describing landscape composition and scenic beauty through visual concepts or attributes [9,[19][20][21]. With regard to Alpine landscapes, several authors discussed attributes like naturalness, wilderness, and diversity and studied the consequences of land-use processes of intensification, abandonment, and reforestation [4,9,19,22]. Tveit et al [20] define naturalness as the closeness to a preconceived natural state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars studying landscape perceptions and preferences argue that people do not only form opinions about the landscape on the basis of the biophysical characteristics of that landscape, but also by 'mental images' (Lindemann-Matthies et al 2010) or conceptions of what a landscape should look like (Terkenli 2001). Such mental images may be based on information, experiences, knowledge, institutions, and social networks.…”
Section: Linking Ess To Wetland Typesmentioning
confidence: 99%